Level of Knowledge of Batu City Hajj Pilgrimages Regarding Self-Medication - Wijaya, Dhani; Syarifuddin, Sadli; Rahmadanita, Fathia Faza; Kho'im, Khoiron Nur; Rochman, Mochammad Cholilur (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 4 (2024): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v4i0.3309, 2025)
The Hajj pilgrimage is a form of worship that requires a stable health condition for its pilgrims. Self-medication is an act of self-medication as an effort to maintain body condition or treat diseases without using a doctor's prescription. Knowledge related to self-medication has an impact on Hajj pilgrims in an effort to maintain or improve their health status in order to achieve Istita'ah before departure for Hajj. East Java Province shows a prevalence of the number of people who do self-medication of 71.61% in 2020 to 84.34% in 2022. The purpose of this study was to analyze the level of knowledge of Batu City Hajj pilgrims regarding self-medication. This study is descriptive observational. Sampling used consecutive sampling technique. Data collection used a questionnaire. The results of the study from 60 Hajj pilgrim samples showed that the highest value of the 4 indicators was the indicator of rational drug use with a percentage of 81% in the "very good" category. The overall results of the Hajj pilgrim knowledge indicator about self-medication were 75.62% in the "good" category. Based on this, it can be concluded that the knowledge of Batu City Hajj pilgrims regarding self-medication is stated as "good".